Keynote: The science that Versailles forgot - Colin Jones (Science Museum Group Journal)
This article is from the keynote presented by Professor Colin Jones at the Versailles: Science and Splendour conference on 13 December 2024. The conference discussed the interconnected history of the eighteenth-century French court and medical and scientific innovations that were fuelled by the resources – both economic and intellectual – available through Versailles before the French Revolution. The conference was concurrent with the opening of the Science Museum’s Versailles: Science and Splendour exhibition, which was open from 13 December 2024 to 21 April 2025. It features a large collection of scientific and medical equipment from Versailles, including a watch designed for Marie Antoinette, Louis XVI’s rhinoceros, and Cassini’s map of the moon. Emphasising and teasing apart the relationship between power and scientific discovery, the conference gathered an international set of academics and was presented in both French and English.